Efektivitas Penggunaan Modul Fisika Multimedia Interaktif Berbantuan Game dengan Model Problem Based Learning terhadap Multiple Intelligence Peserta Didik Kelas X SMA - Oktaweri, Srisa (Universitas Negeri Padang, 2020)
The 2013 curriculum, which began in effect in the 2013/2014 school year, emphasizes the formation of spiritual and social attitudes, knowledge, and skills of students. This is in line with the theory of multiple intelligence which explains that basically humans have a lot of intelligence. The purpose of this study was to investigate the effectiveness of the use of interactive multimedia physics modules assisted by games with the Problem Based Learning model toward multiple intelligence of students. The research design used was one group pretest-posttest. Data collection instruments used in this study were pretest and posttest sheets. The use of physics modules is said to be effective if there is an increase in student learning outcomes after using physics modules. Analysis of effectiveness using the N-Gain method and see an increase in multiple intelligence of students during three meetings using physics modules.The results of the data analysis showed that the interactive multimedia physics module assisted by game with the Problem Based Learning model was effective in increasing multiple intelligence of students. The effective physics modules is shown by the N-Gain value of 0.54 which is in the medium category and there is a tendency to increase multiple intelligence of students during three meetings using physics modules.